Просторовий дизайн павільйону та ринку "Традиції Гуцульщини" у Косові - Ілик, Наталія Віталіївна; Ilyk, Nataliia Vitaliivna (Національний університет "Львівська політехніка", 2024)
Бакалаврська робота на тему «Просторовий дизайн павільйону та ринку “Традиції Гуцульщини” у м. Косів» присвячена розробці архітектурно-просторових рішень для створення сучасного, функціонального та культурно-орієнтованого комплексу, що відтворюватиме традиції та спадщину Гуцульщини. Метою проєкту є створення багатофункціонального простору, який поєднуватиме торговельну, виставкову та рекреаційну функції, сприяючи розвитку місцевого туризму та збереженню нематеріальної культурної спадщини. У першому розділі проаналізовано історико-культурний контекст Гуцульщини, її архітектурні традиції та особливості народного мистецтва. Визначено типологію ринків і павільйонів, вимоги до їхнього просторового дизайну з урахуванням місцевого колориту. Особливу увагу приділено концепції збереження та популяризації нематеріальної культурної спадщини. Другий розділ містить аналіз містобудівної ситуації в м. Косів, функціональне зонування ділянки та аналіз аналогів подібних об'єктів в Україні та за кордоном. Проведено дослідження потреб місцевих жителів та потенційних туристів, що дозволило визначити ключові принципи формування простору. У третьому розділі викладено художньо-проєктні рішення павільйону та ринку. Розроблено архітектурно-планувальні та об’ємно-просторові рішення, обрано матеріали, що гармонійно поєднуються з традиційною гуцульською архітектурою, а також запропоновано принципи організації освітлення та благоустрою території. Створено концепцію, що забезпечує комфорт та естетичну привабливість для відвідувачів. Четвертий розділ містить економічні аспекти проєкту, включаючи орієнтовний розрахунок кошторису та обґрунтування вибору матеріалів з урахуванням їхньої довговічності, екологічності та економічної доцільності.

The Bachelor's thesis, titled "Spatial Design of the 'Hutsul Traditions' Pavilion and Market in Kosiv," focuses on the comprehensive development of architectural and spatial solutions aimed at creating a modern, functional, and culturally-oriented complex. This complex is envisioned to authentically embody and promote the rich traditions and distinctive heritage of the Hutsul region. The overarching goal of this project is to establish a vibrant, multifunctional space that seamlessly integrates commercial activities, exhibition opportunities, and recreational functions. By achieving this, the design directly contributes to the sustainable development of local tourism, fosters economic growth within the community, and, crucially, supports the vital preservation of Hutsulshchyna's intangible cultural heritage. The first section provides an in-depth analysis of the historical and cultural context of Hutsulshchyna, exploring its unique architectural traditions, distinctive building techniques, and the rich peculiarities of its folk art, including ornamentation and craftsmanship. It meticulously defines the typology of traditional markets and pavilions, outlining the specific requirements for their spatial design to authentically reflect the local character and essence. Particular emphasis is placed on understanding the theoretical frameworks and practical approaches for the effective preservation and active promotion of intangible cultural heritage within an architectural context, highlighting its role as a living and evolving aspect of regional identity. The second section thoroughly examines the urban planning situation in the city of Kosiv, including its geographical context, existing infrastructure, and potential for development.Furthermore, a detailed study of the needs and preferences of both local residents and potential tourists was carried out, providing critical insights that directly informed the definition of key principles for the formation and organization of the proposed space, ensuring its relevance and user-centricity. The third section outlines the core artistic and design solutions for the pavilion and market. This includes the development of innovative architectural-planning solutions that optimize space utilization and user experience, alongside detailed volumetric-spatial concepts that define the building's form and relationship with its surroundings. A careful selection of materials was undertaken, prioritizing those that not only harmonize aesthetically with traditional Hutsul architecture but also offer durability, sustainability, and local availability. Principles for integrated lighting design, both natural and artificial, were developed to enhance ambiance and functionality, while comprehensive landscaping strategies were devised to create inviting outdoor spaces that complement the built environment. The resulting concept is designed to ensure maximum comfort, aesthetic appeal, and cultural resonance for all visitors. The fourth section delves into the economic aspects of the project. This includes a detailed estimated cost calculation, considering all phases of design and construction, as well as operational considerations. A thorough justification for the selection of materials is presented, weighing factors such as their long-term durability, environmental impact, sourcing, and overall economic feasibility. This section underscores the project's commitment to creating a sustainable and economically viable complex that offers significant value and contributes positively to the local economy.
Spatial design of the pavilion and market "Traditions of the Hutsul Region" in Kosiv
Keywords: 6.022.03.03; просторовий дизайн; павільйон; ринок; Гуцульщина; традиції; нематеріальна культурна спадщина; Косів; етнодизайн; spatial design; pavilion; market; Hutsulshchyna; traditions; intangible cultural heritage; Kosiv; ethno-design; cultural preservation; sustainable tourism